Thermo-elastohydrodynamic lubrication simulation of the Rayleigh step bearing using the progressive mesh densification method. (May 2019) - Kumar, Rahul; Azam, Mohammad Sikandar; Ghosh, Subrata Kumar; Khan, Hasim
The paper deals with the numerical simulation of thermo-elastohydrodynamic lubrication (Thermo-EHL) condition in the Rayleigh step bearing. Thermo-EHL involves rheology of the lubricant and deformation of the structure simultaneously under the influence of pressure and temperature, which makes this regime of lubrication more complicated. It is difficult to obtain a converged and accurate solution with ease under this condition. The effect of computational mesh density plays a significant role in obtaining a converged solution rapidly. In this paper, the progressive mesh densification (PMD) method has been applied to solve the Thermo-EHL condition numerically. To find out the best possible scheme of PMD for obtaining a converged solution quickly, the results of PMD and fixed mesh density (FMD) have been compared. Based on the comparison, it has been observed that Scheme 3 of PMD takes around 30% fewer iterations compared with FMD under both elastohydrodynamic lubrication (EHL) and Thermo-EHL conditions. Adopting Scheme 3 of PMD, the effect of temperature on the load capacity, coefficient of friction, no-pressure zone, and pressure distribution in the Rayleigh step bearing has been studied. Reductions in pressure, no-pressure zone, frictional coefficient, and load capacity are observed under the Thermo-EHL condition compared to the EHL condition.